Jumlah Isapan Asi Pada Rada’ah - Rifqan, Faaza; Sari, Yopita; Aqsha, Muhammad Rasyid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Giving breast milk (breast milk) in an Islamic perspective has a very important value, not only from a health perspective, but also from a religious teaching perspective. Islam teaches the importance of caring for and educating children with love, one of which is through providing breast milk as the main source of nutrition for newborn babies. In the context of Islamic teachings, the correct number of suckles is an important aspect to ensure successful breastfeeding, which must also be done with full attention and in accordance with religious instructions. Islam not only regulates the duration of breastfeeding, but also emphasizes the importance of the quality of breastfeeding, which can be determined by how often and how effectively the baby breastfeeds.Therefore, this paper aims to discuss further the importance of the number of breast milk sucks during the radha'ah period according to Islamic views, as well as the factors that influence a good breastfeeding process and in accordance with religious teachings, in order to achieve success in providing optimal breast milk for children, and strengthen the relationship between mother and child.